Mouse polyQ database: a new online resource for research using mouse models of neurodegenerative diseases. Issue 1 (December 2015) - Szlachcic, Wojciech; Switonski, Pawel; Kurkowiak, Małgorzata; Wiatr, Kalina; Figiel, Maciej
Abstract Background The polyglutamine (polyQ) family of disorders comprises 9 genetic diseases, including several types of ataxia and Huntington disease. Approximately two decades of investigation and the creation of more than 130 mouse models of polyQ disorders have revealed many similarities between these diseases. The disorders share common mutation types, neurological characteristics and certain aspects of pathogenesis, including morphological and physiological neuronal alterations. All of the diseases still remain incurable. Description The large volume of information collected as a result of the investigation of polyQ models currently represents a great potential for searching, comparing and translating pathogenesis and therapeutic information between diseases. Therefore, we generated a public database comprising the polyQ mouse models, phenotypes and therapeutic interventions tested in vivo. The database is available athttp://conyza.man.poznan.pl/ . Conclusion The use of the database in the field of polyQ diseases may accelerate research on these and other neurodegenerative diseases and provide new perspectives for future investigation.